PEMBERDAYAAN PETERNAK SAPI MELALUI PROGRAM CSR (CORPORATE SOCIAL RESPONSIBILITY) ENERGY EQUITY EPIC (SENGKANG) PTY.LTD DI KECAMATAN GILIRENG KABUPATEN WAJO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The purpose of this study was to determine the model for empowering cattle farmers through the Energy Equity Epic (Sengkang) Pty.Ltd (Corporate Social Responsibility) program and to determine the effectiveness of this cattle farmer empowerment program in Gilireng District, Wajo Regency. This type of research is descriptive qualitative using a sociological approach that is indispensable in research as an effort to systematically identify and study social phenomena that exist in public relations. The results of this study are that there are two models of cattle farmer empowerment used, namely: (1) Rolling Cattle Empowerment Model, and (2) the Cattle Fattening Empowerment Model. The effectiveness of this program itself can be said to be successful, in addition to the objectives of this program is well implemented, the community also experienced an increase in the quality of life to be much better before joining this program. This is indicated by the increase in people's income which has an effect on increasing the economy.